Shape of the dental arch in medicine students - Omarys Chang Calderin; Katiuska Figueredo Villa; Carlos Alberto Albán Hurtado; Marelys Chang Calderin (Editorial Ciencias Médicas, 2021)
Introduction: In humans, the shape and size of the dental arc has been studied for several centuries. The bones of the jaw and maxilla, the position of the teeth, the perioral musculature and the intraoral functional forces determine the shape of the dental arch. Objective: To determine the shape of the dental arcs in students of the School of Medicine of Universidad Nacional de Chimborazo during the period April-August 2019. Methods: A descriptive, cross-sectional and quantitative study is presented; with a universe of 320 students and the sample was formed by 60 of both sexes (female and male), who signed the informed consent. Maxillary and jaw impressions were taken using alginate and made with extra hard Dental Stone in order to identify the type of dental arc according to the table determined by Chuck. Results: In the maxilla, the square shape was observed in 48.30%; continue the ovoid with 38.30% and narrow with 13.30%. In the jaw the narrow shape (36.70%), the ovoid (35.00%) and the square (28.30%). Conclusions: Most of the dental arcs in the maxilla are square; as well as in the mandibular arc the narrow shape. In both cases, the ovoid form continued.